Linguistic Discoveries: Tracing Grammatical Errors in the Translation of Qasas Al-Nabiyyīn by Abu Hasan Ali Hasani Nadwi - Satori, Achmad; Suparno, Darsita; Aqil Assyauqi, Wahyu; Wahidah, Wardah; Anas, Muhammad; Rokhim, Minatur; Zakaizak, Fathalla Muhamed Fathalla (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This article aims to understand the grammatical errors in the translated text of "Qasas Al-Nabiyyīn" by Abu Hasan Ali Hasani Nadwi. This research uses the descriptive qualitative method to identify morphological and syntactic errors in the translated text. Data collection was done by collecting the original text of the source language and its translation in the book "Qasas Al-Nabiyyīn." The data collection steps involved identifying pairs of both languages for grammatical analysis, followed by data analysis to identify grammatical errors. The analysis results showed 18 grammatical errors in the translation of the book, consisting of 7 morphological errors and 11 syntactic errors. These errors impact the incompatibility of the message contained in the source text. In order to correct the grammatical errors, a correction analysis was conducted on the target language, especially in Indonesian, by referring to the applicable grammatical rules. This article concludes that correcting grammatical errors can improve the accuracy and clarity of the message in the translation of "Qasas Al- Nabiyyīn" so that it can be more effectively conveyed to readers who speak the target language. This analysis contributes to a practical understanding of the importance of paying attention to grammatical aspects in translating religious texts. Recommendations for future research include developing more effective translation strategies involving source and target language experts. Research can expand the scope of analysis to explore semantic and pragmatic aspects of translated texts. In addition, further research could consider the impact of cultural context on the understanding and interpretation of religious texts in translation. The results of this study are expected to provide a foundation for developing better translation guidelines, improve the quality of translated religious texts, and facilitate a deeper understanding of essential messages in religious literature.